Field report spring 1978 - Schaufenbuel, Joseph P.et al (1978)
Document titled "field report spring 1978," submitted by Joseph P. Schaufenbuel, May 31, 1978. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of spring, 1978. Epson - sheet feed/flatbed